The effect of plasma-treated nutrient solution on yield, pigments, and mineral content of rocket [Diplotaxis tenuifolia (L.) DC.] grown under different nitrogen fertilization levels - Sodini, Mirko; Traversari, Silvia; Cacini, Sonia; Gonfiotti, Irene; Lenzi, Anna; Massa, Daniele (Frontiers in Plant Science, 2024)
IntroductionThe non-thermal plasma (NTP) technique has been suggested as a sustainable horticultural practice to promote biomass accumulation, nutrient uptake, N metabolism, and disease prevention in plants. In particular, the potentiality of this technique to promote the natural accumulation of nutrients into plants deserve to be explored as input saving is strongly recommended in the horticultural sector.MethodsThe nutrient solution supplied to a red coloured variety of rocket salad [Diplotaxis tenuifolia (L.) DC. ‘Dragon’s Tongue’] grown in a hydroponic close loop system was treated with NTP. Low, medium, and high concentrations of N (i.e., 1, 10, and 20 mM) of the nutrient solution were tested in control (no NTP) or NTP treated conditions in two consecutive growing cycles. Results and discussionResults highlighted a N-dependent effect of NTP treatment showing a biomass stimulation at 10 mM N while negative effects of this technique at 1 and 20mM N. The biomass boosting of NTP found at 10 mMN coupled with an increase in K and Zn showing positive effects also on the nutraceutical aspects. Interestingly, different mechanisms seemed to be involved in the detrimental effects found at low and high N levels, i.e., a lower sensibility to N deficiency at 1 mM and a synergic negative effect of N and NTP in promoting oxidative stress at 20 mM.